Sr/Ca-Ba/Ca systematics of volcanic rocks from the Central Andes, southern Peru, and its implication for Andean magmatism - Onuma, Naoki; Montoya Ramírez, Manuel Abdon (Geochemical Society of Japan, 1984)
Ca, Sr and Ba contents of 186 volcanic rocks (andesites, dacites, rhyolites, basalts, basanites and shoshonites) collected from the central Andes volcanic zone, southern Peru, have been determined by a inductively coupled plasma emission spectrometry. A SB systematics is drawn on a Sr/Ca-Ba/Ca diagram from the data, suggesting that (1) the Andean andesites are derived through a two-stage process: first, generation of a primary magma (alkali basalt type) through partial melting (ca. 1–2%) of a mantle peridotite; second, fractional crystallization of clinopyroxene and/or plagioclase (olivine, orthopyroxene, hornblende and iron oxides) at depths of thick continental crust, (2) the rhyolites share the common primary magma and are derived through the andesitic magma by further plagioclase crystallization, (3) the shoshonites occurred on the continental side of southern Peru also share the common primary magma by further clinopyroxene crystallization. A comparative study of the Andean magmatism on a Sr/Ca-Ba/Ca diagram revealed that primary magmas generated beneath the central Andes, the southern Andes and the South Sandwich Islands volcanic zones are 1–2, 2–5 and 10–20% melts, respectively, derived from a common mantle peridotite with chondritic Sr/Ca and Ba/Ca ratios.